Out of Concern for Human Dignity, Life and Health in Terms of New Solutions in Public Transport - Mielczarek-Mikołajów, Justyna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Transport undoubtedly belongs to the most important branches of the state economy, and at the same time it is one of the most serious civilization threats to human health and life. This is mainly due to pollutant emissions and other transport-related effects, such as road accidents and noise, which contribute to premature deaths or to lung diseases, heart attacks, asthma, anxiety and dizziness. Limiting these negative consequences requires the implementation of the principles of sustainable transport and intelligent transport systems that improve safety and air quality. The detailed analysis will primarily concern legal solutions related to the idea of sustainable transport, including the emphasis on standards resulting from the Act on electromobility and alternative fuels, as well as the analysis of the practice of functioning of ecological solutions during the energy crisis.